2001
DOI: 10.1002/jmv.1016
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal melanomas do not harbour the kaposi sarcoma‐associated human herpesvirus type 8 DNA

Abstract: Anorectal melanomas are similar to cutaneous melanomas with regard to the mode of spread and to the immunophenotype. When compared with patients with cutaneous melanoma, those suffering from anorectal melanoma have a much worse outcome. The etiology of anorectal melanomas is as yet completely unknown. For anatomical reasons, ultra-violet (UV-B) radiation can not cause anorectal melanomas as in cutaneous tumours, that are associated with exposure of the skin to UV-B radiation. As the cytokine interleukin-6 (IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…The causative agent of Kaposi sarcoma, HHV-8 has not been found in anorectal melanomas [23]. At present there is no evidence that sexual practices explain our observation of higher rates of anorectal melanoma among women.…”
Section: Discussionmentioning
confidence: 86%
“…The causative agent of Kaposi sarcoma, HHV-8 has not been found in anorectal melanomas [23]. At present there is no evidence that sexual practices explain our observation of higher rates of anorectal melanoma among women.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, some authors have suggested a possible association with HIV and HHV-8 infection, but data are still controversial. [7][8][9] Anorectal melanoma commonly affects the elderly in their sixth or seventh decade of life, with a 1.7 -fold higher prevalence in Caucasians than in African Americans. 1 Some authors report a possible female predominance, but most publications do not suggest significant gender differences and individual series are too small to draw definitive conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…1 Some authors report a possible female predominance, but most publications do not suggest significant gender differences and individual series are too small to draw definitive conclusions. [7][8][9][10][11] Lesions are usually polypoid, often ulcerated and easy to bleed, with or without pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…The significant increase in the incidence of affected young men in the San Francisco area led to the hypothesis that HIV is involved in the disease development. Involvement of human herpesvirus‐8 and human papilloma virus‐16 has been excluded 8,14 …”
Section: Clinical Featuresmentioning
confidence: 99%